HABITAT AND BIOLOGICAL CHARACTERISTIC OF TILAPIA (Oreochromis niloticus) IN BATUR LAKE - Ni Komang Suryati; Samuel Samuel (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
Study on habitat and biological characteristic of Tilapia (Oreochromis niloticus) in Batur lake have been carried out in Februari until November 2011. The result investigations of water quality parameters at six research station showed that support for the life of Tilapia. Exploitation rate of Tilapia was exceed the optimum rate (over fishing). Tilapia in Batur lake was able to reach 41,45 cm on size with growth rate (K) 0,52 per year. Tilapia in Batur lake was spawn throughout the year (IKG < 20%) with the top of spawning on March and July. The size of first maturity was 17,559 – 20,408 cm. Tilapia in Batur Lake was herbivore to omnivore as the first consumer level with generalis pattern.